cBIN1 Score (CS) Identifies Ambulatory HFrEF Patients and Predicts Cardiovascular Events - Hitzeman, Tara C.; Xie, Yu; Zadikany, Ronit H.; Nikolova, Andriana P.; Baum, Rachel; Caldaruse, Ana-Maria; Agvanian, Sosse; Melmed, Gil Y.; McGovern, Dermot P. B.; Geft, Dael R.; Chang, David H.; Moriguchi, Jaime D.; et al. (Frontiers in Physiology, 2020)
Background: Cardiac Bridging Integrator 1 (cBIN1) is a membrane deformation protein that generates calcium microdomains at cardiomyocyte t-tubules, whose transcription is reduced in heart failure, and is released into blood. cBIN1 score (CS), an inverse index of plasma cBIN1, measures cellular myocardial remodeling. In patients with heart failure with preserved ejection fraction (HFpEF), CS diagnoses ambulatory heart failure and prognosticates hospitalization. The performance of CS has not been tested in patients with heart failure with reduced ejection fraction (HFrEF). Methods and Results: CS was determined from plasma of patients recruited in a prospective study. Two comparative cohorts consisted of 158 ambulatory HFrEF patients (left ventricular ejection fraction (LVEF) ≤40%, 57±10 years, 80% men) and 115 age and sex matched volunteers with no known history of HF. N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentrations were also analyzed for comparison. CS follows a normal distribution with a median of 0 in the controls, which increases to a median of 1.9 (p<0.0001) in HFrEF patients. CS correlates with clinically assessed New York Heart Association Class (p=0.007). During one-year follow-up, a high CS (≥1.9) in patients predicts increased cardiovascular events (43% vs. 26%, p=0.01, hazard ratio 1.9). Compared to a model with demographics, clinical risk factors, and NT-proBNP, adding CS to the model improved the overall continuous net reclassification improvement (NRI 0.64; 95% CI 0.18-1.10; p=0.006). Although performance for diagnosis and prognosis was similar to CS, NT-proBNP did not prognosticate between patients whose NT-proBNP values were >400 pg/mL. Conclusions: CS, which is mechanistically distinct from NT-proBNP, successfully differentiates myocardial health between patients with HFrEF and matched controls. A high CS reflects advanced NYHA stage, pathologic cardiac muscle remodeling, and predicts one-year risk of cardiovascular events in ambulatory HFrEF patients. CS is a marker of myocardial remodeling in HFrEF patients, independent of volume status.